Development of English in Marathi Speaking Children Attending English Medium Schools (Senior Kindergarten and Grade I) - Kottapurathu, Merin Jose; Waknis, Aarti (Innovare Journal of Education, 2023)
An increasing number of Marathi-speaking children attend English medium schools in Maharashtra, India. The developmental trend of English in these children is not studied according to the researcher’s best knowledge. Studying this development is essential to understand the development of children with developmental disabilities. Hence, the study aimed to understand the development of English in Marathi-speaking children attending English medium schools in senior kindergarten and Grade I (5 to 7 years of age). Forty Marathi-speaking children attending English medium schools (Senior Kindergarten and Grade I) were included. ‘Clinical Evaluation of Language Fundamentals Preschool 2nd Edition (CELF)’ was used to assess children's language skills, and ‘Development of Emergent Literacy- Questionnaire’ was administered to study the relation between home literacy environment and language skills in English. A gender difference was present for Senior Kindergarten children but not for the children studying in Grade I. More than 65% of children had scores below the age equivalent scores across the subtests. A moderate positive correlation was found between all the subtests of CELF and the score on the emergent literacy questionnaire. In conclusion, there is an effect of gender on English language skills in kindergarten which is not present in Grade I. The competency in English in Marathi-speaking children appears to be low and moderately related to literacy exposure at home.